2011
DOI: 10.1007/s00299-011-1185-9
|View full text |Cite
|
Sign up to set email alerts
|

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat

Abstract: Expansin protein is a component of the cell wall generally accepted to be the key regulator of cell wall extension during plant growth. Plant hormones regulate expansin gene expression as well as plant growth during drought stress. However, the relationship between expansin and plant hormone is far from clear. Here, we studied the involvement of expansin in plant cell growth mediated by the hormones indole-3-acetic acid (IAA) and abscisic acid (ABA) under osmotic stress which was induced by polyethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 47 publications
0
46
1
1
Order By: Relevance
“…There is increasing evidence demonstrating that expansins are involved in the responsive mechanisms of plant species to water stress (Dai et al, 2012;Zhao et al, 2012;Barcia et al, 2014). Recently, Zhou et al (2015) have suggested that water stress inhibits leaf growth; however, changes in expansin activity and cell wall susceptibility to expansin during times of water deficit could increase the growth rate after rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence demonstrating that expansins are involved in the responsive mechanisms of plant species to water stress (Dai et al, 2012;Zhao et al, 2012;Barcia et al, 2014). Recently, Zhou et al (2015) have suggested that water stress inhibits leaf growth; however, changes in expansin activity and cell wall susceptibility to expansin during times of water deficit could increase the growth rate after rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the regulation by phytohormones, expansin genes are also differentially regulated by various environmental cues [54], such as abiotic stresses including salt stress, heat stress, drought stress, and water stress [30], [37], [43], [70]. Here we tested the germination phenotype of exp2 and the overexpression line in response to salt stress and osmotic stress, and we found that exp2 mutant exhibited hypersensitivity to salt stress and osmotic stress compared to wild type, while the overexpression line showed reduced sensitivity to these stress treatments and revealed enhanced tolerance to stress to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive occurrence of the expansins superfamily in plants suggests that expansins play multiple roles during the plant life cycle [14]–[15], and in the past several decades numerous studies have accumulated evidence about their involvement in diverse developmental processes, including seed germination [16]–[17], seedling morphogenesis [18], root architecture [19]–[26], leaf development [27]–[30], fruit ripening [31]–[32], stoma opening [33]–[34], pollination [35], abscission, stress responses [36]–[43] and others. However, those characterized expansins only represent a small proportion of the expansins superfamily in the plant kingdom, and the individual functions of other expansin coding genes still remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that most hormones that affect the root development seem to act ultimately by modulating auxin activity (Moubayidin et al , 2010; Perilli et al , 2012). Hormones control root development in many ways, one of which is that hormones can change the expression of root cell-wall-loosening protein genes or the activity of cell-wall-loosening proteins (Jan et al , 2004; Liu et al , 2007; Zhao et al , 2012). Regulated cell expansion allows plants to adapt their morphogenesis to survive in different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%